Butler’s “Future State” & Hume’s “Guide of Life” - Russell, Paul (Hybris, 2010)
In this paper I argue that Hume’s famous discussion of probability and induction, as originally presented in the Treatise, is significantly motivated by irreligious objectives. A particular target of Hume’s arguments is Joseph Butler’s Analogy of Religion. In the Analogy Butler intends to persuade his readers of both the credibility and practical importance of the doctrine of a future state of rewards and punishments. The argument that he advances relies on probable reasoning and proceeds on the assumption that our past experience in this life serves as a reliable and effective guide for our expectations concerning a future state. In the relevant sections of the Treatise Hume aims to discredit this religious argument and the practical objectives associated with it.